Paediatric dengue shock syndrome and acute respiratory failure: a single-centre retrospective study - Nutnicha Preeprem; Suwannee Phumeetham (BMJ Publishing Group, 2022)
Objective Dengue shock syndrome (DSS) is a serious health condition leading to paediatric intensive care unit (PICU) admissions and deaths in tropical countries. Acute respiratory failure (ARF) is associated with DSS and is a major cause of dengue deaths. We aimed to identify risk factors associated with ARF in children with DSS.Methods We retrospectively reviewed children with DSS admitted to a PICU from 2010 to 2020 at a tertiary level hospital in Bangkok, Thailand. Patient characteristics, clinical parameters and laboratory data were collected. Multivariable logistic regression analysis was used to identify factors associated with ARF.Results Twenty-six (43.3%) of 60 children with DSS developed ARF and 6 did not survive to day 28. The median (IQR) age was 8.1 years (IQR 4.0-11.0). Fluid accumulation during the first 72 hours of PICU admission was greater in the ARF group compared with the non-ARF group (12.2% (IQR 7.6-21.7) vs 8.3% (IQR 4.4-13.3), p=0.009). In a multivariate analysis at 72 hours post PICU admission, the presence of ˃15% fluid accumulation was independently associated with ARF (adjusted OR 5.67, 95% CI 1.24 to 25.89, p=0.025).Conclusion ARF is an important complication in children with DSS. A close assessment of patient fluid status is essential to identify patients at risk of ARF. Once the patient is haemodynamically stable and leakage slows, judicious fluid management is required to prevent ARF.